Biomass based hydrogen production by dark fermentation — recent trends and opportunities for greener processes. (April 2018) - Kumar, Gopalakrishnan; Shobana, Sutha; Nagarajan, Dillirani; Lee, Duu-Jong; Lee, Kuo-Shing; Lin, Chiu-Yue; Chen, Chun-Yen; Chang, Jo-Shu
Graphical abstract: Highlights: DF is limited by low yields, hence integration with secondary energy recovery methods is essential. Efficient pretreatments for biomass with improved reactor designs increase H2 yields. Consolidated bioprocessing in both native and engineered scenarios is promising. Microalgae and macroalgae biomass are potential alternative feedstocks. A circular biorefinery is proposed: complete conversion of biomass to energy and valuable products. Abstract : The generation of biohydrogen as source of biofuel/bioenergy from the wide variety of biomass has gathered a substantial quantum of research efforts in several aspects. One of the major thrusts in this field has been the pursuit of technically sound and effective methods and/or approaches towards significant improvement in the bioconversion efficiency and enhanced biohydrogen yields. In this perspective, the present contribution showcases the views formulated based on the latest advances reported in dark fermentative biohydrogen production (DHFP), which is considered as the most feasible route for commercialization of biohydrogen. The potential prospects and future research avenues are also presented.